Welsh correspondence of the French Revolution 1789-1802 - Mair Jones, Ffion; Mair Jones, Ffion (Canolfan Uwchefrydiau Cymreig a Cheltaidd Prifysgol Cymru, University of Wales Centre for Advanced Welsh and Celtic Studies, 2018)
Welsh Correspondence of the French Revolution 1789–1802 is a collection of letters written during the years of the French Revolution and the subsequent continental wars. They were sent by or to people resident in Wales, to or from France, Ireland, North America or England, as well as within the boundaries of Wales itself.